The epidemiological aspects of neurocysticercosis in Latin America (Research, Society and Development, 2025)
Neurocysticercosis (NCC) is a helminth infection caused by the larval form, cysticercus, of the cestode Taenia solium, affecting the central nervous system and endemic mainly in Latin America, where it constitutes a serious public health problem. Objective: to expand knowledge about the pathology in endemic regions, highlighting the importance of investigating the epidemiology of NCC in Latin America, identifying the main risk factors, geographic distribution, temporal trends, and impact on public health. Methodology: data were obtained from scientific databases such as PubMed, Scielo, BVS, Pan American Health Organization (PAHO), CAPES Journals, and LILACS, in English, Portuguese, and Spanish. Results and Discussion: 17 articles were used, which highlight how NCC remains a serious public health problem, associated with poverty, inadequate basic sanitation, pig farming without sanitary control, and limited access to health services. The disease is a reflection of profound structural inequalities, with underreporting being a significant challenge due to the complexity of diagnosis, which requires imaging tests. Conclusion: controlling NCC is one of the greatest challenges in Latin America and requires investments in health education, improved epidemiological surveillance, proper environmental management, and sustainable practices in pig farming to interrupt the parasite's transmission cycle.